1998
DOI: 10.1242/dev.125.22.4349
|View full text |Cite
|
Sign up to set email alerts
|

Transducing positional information to the Hox genes: critical interaction of cdx gene products with position-sensitive regulatory elements

Abstract: Studies of pattern formation in the vertebrate central nervous system indicate that anteroposterior positional information is generated in the embryo by signalling gradients of an as yet unknown nature. We searched for transcription factors that transduce this information to the Hox genes. Based on the assumption that the activity levels of such factors might vary with position along the anteroposterior axis, we devised an in vivo assay to detect responsiveness of cis-acting sequences to such differentially ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our proposed model synthesises previous findings showing that WNT-driven posterior axial identity acquisition in neural derivatives of NMPs takes place prior to neural induction ( Lippmann et al, 2015 ; Metzis et al, 2018 ; Neijts et al, 2017 ; Neijts et al, 2016 ; Takemoto et al, 2006 ) with data illustrating that temporally discrete modes of trunk axial patterning in CNS spinal cord/NC rely on both FGF and WNT activities ( Bel-Vialar et al, 2002 ; Delfino-Machín et al, 2005 ; Dunty et al, 2014 ; Hackland et al, 2019 ; Liu et al, 2001 ; Mazzoni et al, 2013 ; Mouilleau et al, 2021 ; Muhr et al, 1999 ; Nordström et al, 2006 ; Sanchez-Ferras et al, 2016 ; Sanchez-Ferras et al, 2014 ; Sanchez-Ferras et al, 2012 ; van Rooijen et al, 2012 ; Zhao et al, 2014 ). Our work also reflects results showing the existence of distinct phases of Hox gene expression program implementation in vivo : (i) an early ‘plastic’ phase linked to A-P patterning of multipotent axial progenitors/NMPs within their posterior niche and (ii) a later phase, which marks the instalment and fixing of lineage-specific Hox gene expression patterns and the sharpening of their final boundaries in the neural and mesodermal derivatives of axial progenitors as and after they exit the posterior growth zone ( Ahn et al, 2014 ; Brend et al, 2003 ; Charité et al, 1998 ; Deschamps and Wijgerde, 1993 ; Forlani et al, 2003 ; Hayward et al, 2015 ; McGrew et al, 2008 ; Wymeersch et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our proposed model synthesises previous findings showing that WNT-driven posterior axial identity acquisition in neural derivatives of NMPs takes place prior to neural induction ( Lippmann et al, 2015 ; Metzis et al, 2018 ; Neijts et al, 2017 ; Neijts et al, 2016 ; Takemoto et al, 2006 ) with data illustrating that temporally discrete modes of trunk axial patterning in CNS spinal cord/NC rely on both FGF and WNT activities ( Bel-Vialar et al, 2002 ; Delfino-Machín et al, 2005 ; Dunty et al, 2014 ; Hackland et al, 2019 ; Liu et al, 2001 ; Mazzoni et al, 2013 ; Mouilleau et al, 2021 ; Muhr et al, 1999 ; Nordström et al, 2006 ; Sanchez-Ferras et al, 2016 ; Sanchez-Ferras et al, 2014 ; Sanchez-Ferras et al, 2012 ; van Rooijen et al, 2012 ; Zhao et al, 2014 ). Our work also reflects results showing the existence of distinct phases of Hox gene expression program implementation in vivo : (i) an early ‘plastic’ phase linked to A-P patterning of multipotent axial progenitors/NMPs within their posterior niche and (ii) a later phase, which marks the instalment and fixing of lineage-specific Hox gene expression patterns and the sharpening of their final boundaries in the neural and mesodermal derivatives of axial progenitors as and after they exit the posterior growth zone ( Ahn et al, 2014 ; Brend et al, 2003 ; Charité et al, 1998 ; Deschamps and Wijgerde, 1993 ; Forlani et al, 2003 ; Hayward et al, 2015 ; McGrew et al, 2008 ; Wymeersch et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine if Hox and Cdx members interacted on common target promoters, we used a ChIP−re-ChIP approach to assess the occupancy of the Hoxb8 regulatory element, which is Cdx target. 18,28 To this end, P19 cells were transfected with Cdx1 in combination with Hoxd4 or Hoxd4 R,R,R→G,G,G and the response element. As expected, Cdx1, Hoxd4, and Hoxd4 R,R,R→G,G,G were all enriched at this locus (data not shown), and mutation of Hoxd4 did not abrogate its ability to bind to DNA (Figure 5B, right panel).…”
Section: ■ Resultsmentioning
confidence: 97%
“…To determine if the interaction between Cdx1 and Hox proteins has potential biological impact, we assessed the effect of coexpression of Cdx1 and Hoxd4 on transcription directed by the Hoxb8 promoter region, which contains four consensus Cdx binding sites that can be driven by Cdx1. 18 Transfection analyses in P19 embryocarcinoma cells revealed that Cdx1 and Hoxd4, but not Cdx1 and Hoxd4 R,R,R→G,G,G , activated this reporter (Figure 5C). These data are consistent with the physical interaction between Cdx and Hox having an impact on transcription of at least some common target genes.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations